Searching for Accreting Compact Binary Systems from Spectroscopy and Photometry: Application to LAMOST Spectra - Zhao, Xinlin; Wang, Song; Liu, Jifeng (The Astrophysical journal, 2025)
Compact objects undergoing mass transfer exhibit significant (and double-peaked) H α emission lines. Recently, new methods have been developed to identify black hole X-ray binaries and calculate their systematic parameters using H α line parameters, such as the full width at half-maximum (FWHM), equivalent width (EW), and separation of double peaks. In addition, the FWHM–EW plane from spectroscopy and the H α color–color diagram from photometry can be used for rapid stellar classification. We measure the H α and H β profiles (e.g., FWHM and EW) using the LAMOST DR9 low- and medium-resolution spectra, and calculate the systematic parameters (e.g., velocity semiamplitude of the donor star, mass ratio, inclination angle, and mass of the accretor). A new correlation between FWHM and K 2 , K 2 = 0.205(18) FWHM, is obtained for cataclysmic variables (CVs) in our sample. Both the FWHM–EW plane and the H α color–color diagram can distinguish CVs with FWHM ≳ 1000 km s −1 from Be stars and young stellar objects to some extent. To improve classification accuracy and enhance the selection of compact objects, we propose a new set of idealized filters with effective widths of 30, 130, and 400 Å for the narrow H α filter, broad H α filter, and r -band filter, respectively.